O Sentido das Decisões. O processo de projecto de duas casas em Lago, Amares - Ana Rita Gomes Correia (2019)
This dissertation, presented under the title "The meaning of decisions. The process of designing two houses in Lago, Amares", will result from the search for a personal approach to a project methodology, not as a simply mechanical and functional act, but as a process of authorship, and in this sense, arbitrary and intuitive, motivated by the launching and selection of assumptions, hypotheses, references, theory and history. Due to the complexity and extension of this theme, this work reflects a necessarily personal position, supported in texts by authors, along with my way of thinking, and the quest to do architecture. The project of two holiday homes will support the narration of the "story". This narrative will convene some themes, which will serve as the basis for reflection on the design process and justify decisions throughout the project. The objective of this work will be to become more aware of the project methodology for a better definition of a project strategy, which will lead to the understanding of key moments and, consecutively, to the final result of the proposal. In short, it will not be a conclusive process, but it is assumed as one of several points of view, among the many possible ways of approaching the creative process, being aware that it would be impossible to deepen all concepts.